[Workplace smoking project, program strategy] (Tufts Archival Research Center, 2007)
Program strategy for the workplace smoking project. Identifies the objective of the program as discouraging legislators from discriminating against smokers and lists resources helpful in doing so. Lists the different strategies for achieving this goal and the tactics employed.